Смарт-технології в діяльності торгово-промислових палат: перспективи цифрових сервісів для підприємців - Кропівна, Альона Володимирівна; Kropivna, Alona (ЦНТУ, 2025)
Мета кваліфікаційної роботи полягає у проведенні аналізу та оцінки впровадження смарт-технологій у діяльності торгово-промислових палат на прикладі Кіровоградської регіональної ТПП та визначення перспектив розвитку цифрових сервісів для підприємців регіону. The purpose of the qualification thesis is to conduct an analysis and assessment of the implementation of smart technologies in the activities of chambers of commerce and industry, using the Kirovohrad Regional Chamber of Commerce and Industry as a case study, and to identify prospects for the development of digital services for entrepreneurs in the region.
Smart technologies in the activities of chambers of commerce and industry: prospects of digital services for entrepreneurs
Keywords: смарт-технології; цифрові сервіси; цифровізація; smart technologies; digital services; digitalisation